FARMERS SAFETY: Penguatan P3K Keluarga dalam Pencegahan dan Penatalaksanaan Kecelakaan Kerja Sawit - Putri, Silvia Elki; Rayendra, Rozar; Gasril, Pratiwi; Alfidin, Alfaizun Nur; Zhafira, Maulia; Hidayani, Suci; Illahi, Aulia Wahyu (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2023)
Farmer safety is an innovative program as a quick response to palm oil work accidents by strengthening first aid for families. The aim of farmer safety is to increase family knowledge, attitude and skill in providing health care to family members who experience oil palm work accident at palm oil harvesters. The activity method is carried out in two stages. The first stage is literature study and preparing of first aid tools and materials. The second stage is a location survey, program introduction and coordinating with partners, socialization of farmer safety and health education, training and mentoring, evaluation and monitoring. This activity was carried out in Karya Bhakti Village, Kampar Kiri Tengah District, Kampar Regency, Riau Province. The target of this activity is the Pemberdayaan dan Kesejahteraan Keluarga (PKK) group which is an active Human Resources (HR) in Village level association. The number of participants are 30 people. The partners for this activity are the Community Health Center, the Village Government, and the PKK group in Karya Bhakti Village. The results of this activity were a 98% increase in knowledge, a 95% increase in attitudes, an increase in skills in handling and preventing palm oil work accidents, and 90% of partners were very satisfied after being given the farmer safety program. This activity is beneficial for health, economic and welfare, educational and social aspects. It is hoped that this activity will be integrated into the Occupational Health Unit Post (UKK) managed by the Community Health Center. Farmer safety as a form of realization in supporting the Government's program to reduce poverty, end hunger, good health and prosperity, decent work and economic growth as well as supporting the Healthy Indonesia Program with a Family Approach (PISPK) through optimizing the implementation of UKK Posts managed by Community Health CentersÂ (Puskesmas).